Non-employment over the working life: Implications for cognitive function and decline in later life - A.J. Sizer; A. Sacker; R.E. Lacey; M. Richards (Public Health in Practice)
Objectives: Disuse theory predicts that cognitive function is vulnerable to transitions that remove factors that support cognitive skills. We sought to investigate whether non-employment over the working life was associated with cognitive function and decline in later life (≥60 years old), and possible gender differences in the association. Study design: Longitudinal study. Method: We used data from the MRC National Survey of Health and Development (NSHD). Cognitive function was measured by verbal memory and processing speed. Linear regression was used to test associations between non-employment duration and cognitive function at age 60–64, and conditional change models were used to examine associations between non-employment and cognitive decline from age 60–64 to 69. Gender specific models were adjusted for childhood factors and educational attainment, adult occupational features, and adult health and lifestyle indicators. Missing data was accounted for using multiple imputation by chained equations. Results: In fully adjusted models >15 years non-employment was associated with lower cognitive function at age 60–64 in men (verbal memory: −0.72, 95%CI −1.18, −0.26; processing speed: −0.61, 95%CI -1.00, −0.28), but not women. Fully adjusted models also indicated that long-term and intermediate lengths of non-employment were associated with faster decline in verbal memory (−0.38, 95%CI -0.75, −0.02) and processing speed (−0.28, 95%CI -0.52, −0.03) in men. There was no association between non-employment and cognitive decline among women. Conclusion: Long-term non-employment in men, but not women, is associated with accelerated cognitive ageing.